Perhalogenated tetraazaperopyrenes and their corresponding mono- and dianions - Günther, Benjamin; Wadepohl, Hubert; Gade, Lutz H. (Organic letters, 2020)
Chlorination and bromination of 2,9-perfluoropropyl-substituted tetraazaperopyrenes (TAPPs) under forcing conditions resulted in fully core-halogenated TAPP derivatives, devoid of hydrogen atoms at the polycyclic aromatic core. The octahalogenation stabilized the reduced mono- and dianionic compounds sufficiently to allow for their characterization. The additional ortho-chlorination led to an improvement of the electron mobility compared to the bay-substituted tetrachloro-TAPP when employed as an n-channel semiconductor in thin-film transistors.